SECURITY ANALYSIS OF WIRELESS NETWORKS USING WEP-TECHNOLOGIES - Юдін, О.; Весельська, О. (Science-based technologies, 2012)
In the article the quality of information security in wireless networks by using WEP-encryption scheme and RC4 symmetrical streaming algorithm was studied. The tips and ways to improve the security of information are given.